2020
DOI: 10.1186/s43094-020-00056-8
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm potential of Psidium guajava and Passiflora edulis pulp extracts against Staphylococcus aureus, cytotoxicity, and interference on the activity of antimicrobial drugs

Abstract: Background Pathogenic strains of Staphylococcus aureus can cause several diseases including septicemia and endocarditis, in spite of being a commensal species of the human microbiota. The current drug resistance of S. aureus raises the need for new antimicrobials, and natural products represent a feasible source for prospection of such compounds, due to features including the diversity of structures and mechanisms of action. Here, we provide evidence of the antimicrobial activity of methanolic of Psidium guaja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The MBEC (Minimum Biofilm Eradication Concentration) reported by dos Santos et al ( 44 ) (250 μg/ml) is lower than those reported by Dutta et al ( 69 ) (1,000–2,100 μg/ml). This could indicate that probably the guava leaf extract has a higher activity compared to the compound Benzyl isocyanate (isolated from guava leaves) on its own.…”
Section: Antimicrobial Effects Of Psidium Guajava Lmentioning
confidence: 52%
See 2 more Smart Citations
“…The MBEC (Minimum Biofilm Eradication Concentration) reported by dos Santos et al ( 44 ) (250 μg/ml) is lower than those reported by Dutta et al ( 69 ) (1,000–2,100 μg/ml). This could indicate that probably the guava leaf extract has a higher activity compared to the compound Benzyl isocyanate (isolated from guava leaves) on its own.…”
Section: Antimicrobial Effects Of Psidium Guajava Lmentioning
confidence: 52%
“…Nonetheless, an aspect to consider during the use of industrial byproducts is the possible presence of food additives, as is the case of the pulp extract used by dos Santos et al ( 44 ), which contained different additives, among them, the antioxidant BHT, which may cause allergies, eczema, rash, and angioedema, therefore BHT cannot exceed an ADI of 0.5 mg/kg ( 48 ). As the presence of these additives probably remains after the extraction and can affect the activity of the extract, it is important to determine in what concentrations are they found in the plant material and what are the possible toxicological effects that they may cause depending on the route of administration.…”
Section: Phytochemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…HepG-2 and K-562 cells were grown in Rosewell Park Memorial institute medium (RPMI-1640) (Sigma Aldrich, USA) supplemented with 50 µg/ml gentamycin and 10% inactivated fetal calf serum. The cells were kept at 37ºC in a humidified atmosphere with 5% CO 2 and were sub-cultured two to three times a week (Cruz et al 2020 ; dos Santos et al 2020 ). On the other hand, MRC-5 cells were propagated in Dulbecco’s modified Eagle’s medium (DMEM) (Sigma Aldrich, USA) containing 10% heat-inactivated fetal bovine serum, HEPES buffer (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid), 1% L-glutamine, and 50 µg/ml gentamycin.…”
Section: Methodsmentioning
confidence: 99%
“…There abounds, in the literature, evidence of anti-bacterial and anti-biofilm properties of plant materials that can be harnessed for combating antimicrobial resistance of pathogenic organisms by interrupting the biofilm formation system. For instance, various parts of P. guajava have been reported for anti-biofilm activities against Staphylococcus aureus (250 μg/mL of pulp extract) [12], Streptococcus mutans and Streptococcus gordonii (0.78 mg/mL of leave extract) [28]. Fu et al also reported that aqueous extract of Herba patriniae exhibited an inhibitory effect on almost all the studied biofilm-related genes of Pseudomonas aeruginosa with a significant reduction in the formation of biofilm as well as an alteration in the structure of the mature biofilms.…”
Section: Introductionmentioning
confidence: 99%